Women's involvement in terrorist organizations - Sloan, Melissa Marie (Gender and crime, 2024)
In most academic and media reports, terrorists are assumed to be men. However, throughout history, women have had important roles in the formation, sustenance, and lethality of major terrorist organizations worldwide. In this chapter, we explore three themes regarding women’s involvement in terrorist groups: (1) women’s motivation and recruitment, (2) the roles of women in violent groups, and (3) the strategic benefits of female recruitment in terrorist groups. We then present a case study of women in the Kurdistan Worker’s Party (PKK) as an illustration of the diverse factors that shape their participation in terrorism and the agency that many female terrorists exert in their decision to join insurgent groups. In order to develop effective and comprehensive counterterrorism strategies, it is essential that policymakers understand the roles that women play in terrorist organizations and recognize the diverse pathways that they take into terrorism.